Switch to etravirine for HIV‐positive patients receiving statin treatment: a prospective study. (July 2015) - Ciaffi, Laura; Cavassini, Matthias; Genne, Daniel; Delhumeau, Cecile; Spycher Elbes, Rachel; Hill, Andrew; Wandeler, Gilles; Fehr, Jan; Stoeckle, Marcel; Schmid, Patrick; Hirschel, Bernard; Montecucco, Fabrizio; et al.
Abstract Background Lifestyle changes and statins are the cornerstones in management of dyslipidaemia in patients with HIV infection. Replacement of an antiretroviral therapy (ART) component is a proposed therapeutic strategy to reduce cardiovascular risk. In dyslipidaemic patients with HIV infection, we assessed the efficacy of replacing boosted protease inhibitor (bPI) or efavirenz (EFV) by etravirine (ETR) as an alternative to statin therapy. Materials and methods A prospective, open‐label, multicentre, 12‐week study of patients with HIV infection on ART including bPI or EFV, and statin treatment. Four weeks after statin interruption, bPI or EFV was switched to ETR (400 mg, 8 weeks) if serum low‐density lipoprotein cholesterol (LDL‐C) was ≥ 3 mM. The primary endpoint was the proportion of patients on ETR with no indication for statin treatment at study completion. Serum levels of HIV RNA, lipids and biomarkers of cardiovascular disease were also measured. (ClinicalTrials.gov: NCT01543035). Results The 31 included patients had a HIV‐1 RNA < 50 copies/mL (median age, 52 years; median CD4, 709 cell/mL; median LDL‐C, 2·89 mM), 68% were on EFV, and 32% were on bPI. At week 4, 27 patients switched to ETR. At study completion, 15 patients (56%) on ETR did not qualify for statin treatment. After the ETR switch, serum levels of the cardiovascular biomarkers sICAM and MCP1/CCL2 decreased by 11·2% and 18·9%, respectively, and those of CCL5/RANTES and tissue inhibitor of metalloproteinase‐1 increased by 14·3% and 13·4%, respectively, indicating reduced cardiovascular risk. There were no notable treatment‐related adverse events. Conclusions Replacing bPI or EFV by ETR is a viable strategy to obviate primary prevention statin treatment.